Meningkatkan Customer Engagement dengan Brand Experience dan Visual Brand Communication : (Survei pada Pengguna Scarlett Whitening di Kota Tasikmalaya Jawa Barat) - Ramadhan Dwi Cahya; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to determine the analysis of increasing customer engagement with brand experience and visual brand communication (survey of Scarlett Whitening users in Tasikmalaya City, West Java). The method used in this research is causality through a survey approach. With a research sample of 100 Scarlett Whitening users in Tasikmalaya City, West Java. The data used is primary data. The analytical tool used in this research is multiple regression using SPSS 26.0. The research results show that the Brand Experience obtained from the Brand Experience of Scarlett Whitening Users in Tasikmalaya City, West Java has good criteria. Visual Brand Communication at Scarlett Whitening di Kota Tasikmalaya Jawa Barat has good assessment criteria, Customer Engagement for Scarlett Whitening Users in Tasikmalaya City, West Java has good criteria. Together Brand Experience and Visual Brand Communication have a significant influence on Customer Engagement. Partially, Brand Experience has a significant influence on Customer Engagement. Partially, Visual Brand Communication has a positive and significant effect on Customer Engagement.